2017
DOI: 10.5539/gjhs.v9n8p107
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated and Response to Needle Stick Injuries among Nursing Officers in District General Hospitals of Sri Lanka

Abstract: Introduction: This study was carried out to find out the existing prevalence rates of the Needle Stick Injuries (NSIs) among nursing officers in Sri Lankan health delivery system and to identify the factors associated with NSIs including the level of knowledge, attitude and practice on prevention.Methods: A descriptive cross sectional study was conducted in three District General Hospitals. Five routine working units identified from each hospital. Proportional allocations were made with a final step of simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
5
1
Order By: Relevance
“…The prevalence in this study is lower than the figure from earlier studies in Southwest Ethiopia (58.8%) [ 44 ]; Sri Lanka (43%) [ 22 ]; Thailand Regional Hospital (55.5%) [ 16 ]; Iran Shiraz University Hospital (54%) [ 20 ]; Nigeria (55.8%) [ 57 ]; Dessie, Ethiopia (43%) [ 66 ]; Saudi Arabia (50.9%) [ 67 ]; Egypt (62.3%, 67.9%) [ 68 ]; Sarajevo, Bosnia and Herzegovina (61.1%) [ 69 ]; Jimma, Ethiopia (44.12) [ 70 ]; Hawassa, Ethiopia (46%) [ 47 ]; Pakistan (66%) [ 71 ]; and Jordan (67.6%) [ 21 ]. However, this result is much lower when compared with a study done in Bahir Dar, Ethiopia (66.6%) [ 37 ]; South Korea (74.4%) [ 14 ]; Pakistan (67%) [ 15 ]; and Nepal (74%) [ 18 ].…”
Section: Discussioncontrasting
confidence: 83%
“…The prevalence in this study is lower than the figure from earlier studies in Southwest Ethiopia (58.8%) [ 44 ]; Sri Lanka (43%) [ 22 ]; Thailand Regional Hospital (55.5%) [ 16 ]; Iran Shiraz University Hospital (54%) [ 20 ]; Nigeria (55.8%) [ 57 ]; Dessie, Ethiopia (43%) [ 66 ]; Saudi Arabia (50.9%) [ 67 ]; Egypt (62.3%, 67.9%) [ 68 ]; Sarajevo, Bosnia and Herzegovina (61.1%) [ 69 ]; Jimma, Ethiopia (44.12) [ 70 ]; Hawassa, Ethiopia (46%) [ 47 ]; Pakistan (66%) [ 71 ]; and Jordan (67.6%) [ 21 ]. However, this result is much lower when compared with a study done in Bahir Dar, Ethiopia (66.6%) [ 37 ]; South Korea (74.4%) [ 14 ]; Pakistan (67%) [ 15 ]; and Nepal (74%) [ 18 ].…”
Section: Discussioncontrasting
confidence: 83%
“…This was also shown by a similar study showing 45.1% of NSI incidence in medical wards and 13.3% incidence in surgical wards. 3 This study simultaneously evaluated the difference in NSI incidence rates for the safety cannulae and conventional cannulae over the same study period in the same hospital, while the majority of previous studies done internationally compared data received from different locations and different periods.…”
Section: Discussionmentioning
confidence: 99%
“…2 A descriptive cross-sectional study conducted in 2014 found a 43% prevalence of a history of needle stick injuries in healthcare workers in three District General hospitals in Sri Lanka. 3 The same study showed intravenous cannulation as the most hazardous procedure, as 51% of NSIs occured during cannulation.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations